Alaskapox amid New Orthopox Viral Infections Mikhail V. Supotnitskiy - M. V. Supotnitskiy (Вестник войск РХБ защиты)
A previously unknown virus from the orthopoxvirus family (OPXV) caused a series of smallpox-like diseases among the inhabitants of Alaska. A patient with immunodeficiency died from a generalized infection similar to smallpox. The virus was named Alaska smallpox virus (AKPV).The aim of the study was to summarize the available information on the nature and danger to humans of AKPV and its epidemic significance in the context of other activated orthopoxviruses.Materials and methods. English-language sources available through the PubMed and Google Scholar databases were used. The information was analyzed from the specific to the general. The biological and other properties of AKPV were compared with those of known OPXV.Discussion. AAKPV is related to New World OPXV, but is closely related to Old World OPXV. The clinical picture of the disease caused by AKPV and other OPXVs has a number of common symptoms, collectively called orthopoxvirus syndrome. It is characterized by an initial prodromal period in the form of fever, malaise, headache, myalgia and, less commonly, nausea and vomiting. After an incubation period of 10 to 14 days, macules, papules, vesicles, pustules, ulcers, dry crusts and depigmented scars develop over the course of weeks against the background of lymphadenopathy. In immunocompromised patients, OPXVs can cause a fatal infection resembling smallpox. If this syndrome is detected in a patient, OPXV infection should be assumed and the patient should be managed according to the guidelines of MP 3.1.0291-22. There is also a risk of using any detected OPXV as a source of genes for gain-of-function modification of other pathogens or for simulating.Conclusion. The penetration of AKPV into human populations is part of the process of activation of natural foci of OPXV. The phylogenetic position of AKPV suggests that it may have natural reservoirs not only in Alaska, but also in the boreal forest zone of Russia from Kamchatka to Karelia. Artificial global spread of monkeypox of the lowinfectivity WA clade shows that social engineering techniques combined with global propaganda can simulate OPXV pandemics even with species thought incapable of such spread.